2012 6th European Conference on Antennas and Propagation (EUCAP) 2012
DOI: 10.1109/eucap.2012.6205923
|View full text |Cite
|
Sign up to set email alerts
|

Designing microwave patch antennas using heterogeneous substrates

Abstract: Abstract-This paper introduces the concept of designing microwave patch antennas by creating synthetic heterogeneous substrates with small scale inclusions. These inclusions embedded in a host dielectric can be used to control the dielectric properties and create bespoke effective permittivity values. Heterogeneous patch antennas at 2.4GHz are simulated in this paper. By deliberately mapping the permittivity values to the electric fields, the antenna behavior can be controlled and a dual band frequency was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The results show good agreement with the resonant frequency of the heterogeneous substrate (3.21 GHz) being slightly lower than that of the homogenous equivalent (3.25 GHz). Previous work by the authors in [22], [23] have shown this to be the case for spherical and metallic inclusions. The radiation efficiencies are 93.52% and 92.82% for the homogenous and heterogeneous respectively which again show good agreement.…”
Section: Patch Antennamentioning
confidence: 65%
“…The results show good agreement with the resonant frequency of the heterogeneous substrate (3.21 GHz) being slightly lower than that of the homogenous equivalent (3.25 GHz). Previous work by the authors in [22], [23] have shown this to be the case for spherical and metallic inclusions. The radiation efficiencies are 93.52% and 92.82% for the homogenous and heterogeneous respectively which again show good agreement.…”
Section: Patch Antennamentioning
confidence: 65%
“…In [21] patch antennas above substrates with small scale inclusions where the effective permittivity varied locally were examined. The simulated efficiencies were similar to the homogenous patch antenna.…”
Section: Antenna Designmentioning
confidence: 99%